Effect of the use of ovaprim® on the spawning of kissing gourami (Helostoma temminckii) at UPR Doa Mandeh, Ogan Ilir - Yonarta, Danang; Syafaa’uddin, Abdul Ma’ruf; Fitrani, Mirna; Rarassari, Madyasta Anggana (Universitas Wiralodra, 2025)
The kissing gourami (Helostoma temminckii) is a freshwater species increasingly cultivated in controlled aquaculture systems. However, its production is hindered by the limited availability of broodstock and fry, which still heavily depend on natural catches that fluctuate seasonally. To address this challenge, controlled environment aquaculture offers a sustainable solution to boost the kissing gourami population. One effective method is semi-natural spawning through gonadotropin hormone induction using Ovaprim®, which promotes year-round reproductive readiness in broodstock. This study aims to apply and evaluate the semi-natural spawning technique of kissing gourami using Ovaprim® at UPR Doa Mandeh, Ogan Ilir. Conducted between August and September 2024, the research compared two treatments: natural spawning (P0) and semi-natural spawning (P1). The findings demonstrated promising results, with a fecundity of 9,619 eggs, a fertilization rate of 90.4%, a hatching rate of 94%, and a survival rate of 95%. Water quality parameters remained within optimal ranges, with broodstock pond temperatures between 30–30.6°C and pH levels of 7.27–7.53, while the rearing aquarium maintained a temperature of 31°C and a pH of 7.62–7.66. These results highlight the potential of semi-natural spawning using Ovaprim® as a viable approach for enhancing kissing gourami reproduction, reducing dependency on wild populations, and supporting sustainable aquaculture practices.